Features of severe asthma response to anti-IL5/IL5r therapies: identikit of clinical remission - Carpagnano, Giovanna Elisiana; Portacci, Andrea; Nolasco, Santi; Detoraki, Aikaterini; Vatrella, Alessandro; Calabrese, Cecilia; Pelaia, Corrado; Montagnolo, Francesca; Scioscia, Giulia; Valenti, Giuseppe; D’Amato, Maria; Caiaffa, Maria Filomena; et al. (Frontiers in Immunology, 2024)
Introduction: Clinical remission (CliR) achievement has been recognized as a new potential outcome in severe asthma. Nevertheless, we still lack a detailed profile of what features could better identify patients undergoing clinical remission. In this study, we aim to address this issue, tracing a possible identikit of patients fulfilling remission criteria.We enrolled 266 patients with severe eosinophilic asthma (SEA) treated with a 12-month course of anti-IL5/IL5 receptor (IL5r) monoclonal antibodies. Patients with no exacerbation, OCS withdrawal, ACT ≥ 20 and FEV1 ≥ 80% after 1 year of biologic treatment were classified as in clinical remission.Results: 30.5% of the enrolled patients achieved remission after biologic administration. CliR group showed a lower number of baseline asthma exacerbations and better lung function parameters, with a trend for higher ACT scores and a less frequent history of a positive skin prick test. CliR achievement was unlikely in presence of a higher BMI, a positive skin prick test, an increased number of asthma exacerbations before biologic treatment, anti-muscarinic administration, and a previous diagnosis of EGPA, bronchiectasis or osteoporosis. In contrast, a better lung function, an increased blood eosinophilic count, the presence of chronic rhinosinusitis with nasal polyps and a more frequent use of reliever therapy predicts remission development. Changes in exacerbations number, OCS use, ACT scores and FEV1% between remittent and non-remittent patients arise at specific follow up timepoints and are positively associated with CliR achievement.Discussion: anti-IL5/IL5r biologics can induce CliR in a proportion of patients with SEA. Patients achieving remission demonstrate specific clinical, functional and inflammatory features, as well as a specific moment of improvement in all the CliR items.